Examining the compatibility of energetic plasticizer DNDA-5 with energetic binders - Vijayalakshmi, R.; Agawane, N. T.; Talawar, M. B.; Khan, Md Abdul Shafeeuulla (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2020)
The requirement of developing energetic binders with suitable energetic plasticizers is to enhance the mechanical properties and to reduce glass transition temperature of propellant and explosive formulations. Compatibility of energetic plasticizer 2,4-dinitro-2,4-diazapentane (DNDA-5) with four different energetic binders viz. poly glycidyl nitrate (PGN), poly(3-nitratomethyl-3-methyloxetane) (PLN), glycidyl azide polymer (GAP) and tetra functional glycidyl azide polymer (t-GAP) was studied by using differential scanning calorimeter (DSC) and density functional theory (DFT) methods. Results obtained for the pure binder was compared with the results obtained for binder/plasticizer blend in the parameters of decomposition temperature and the format of the peak which indicated the compatibility or incompatibility of DNDA-5 with the studied binders. Glass transition temperatures of all these blends were determined by low temperature DSC and showed desirable lowering of glass transition temperature with single peak in the case of PLN. The proposed energetic plasticizer DNDA-5 has displayed its compatibility with three binders PGN, PLN and GAP employing thermal techniques. DNDA-5 has been found as incompatible when it is mixed with t-GAP. The predicted relative trend of interaction energies between plasticizer and binder has provided concurrence to results drawn from thermal studies.
Keywords: Computational study; DNDA-5; Glass transition temperature; plasticizing effect; thermal

Computational insights into the iron-catalyze d magnesium-me diate d hydroformylation of alkynes - Sharma, Himanshu; Tewari, Tanuja; Chikkali, Samir H.; Vanka, Kumar (Journal of Organometallic Chemistry, 2023)
Iron is one of the most abundant transition metals in the earth's crust. It has attracted a lot of attention due to its low toxicity, bio-compatibility, and high natural abundance. Iron-catalyzed hydroamination, hydroalkoxylation, hydrocarboxylation, hydrosilylation, hydroboration, hydrophosphination, hydromagnesiation, and carbonylation reactions have therefore been developed over the past decades. However, despite many experimental and theoretical studies, a complete mechanistic understanding of iron-catalyzed hydrofunctionalisation at the molecular level has not yet been achieved. In this work, through density functional theory (DFT) calculations, we have shown the most feasible path for the hydroformylation of alkynes for an experimentally studied system. We have looked at the iron salt as a precatalyst without any external donor ligand, and the calculations revealed that hydrometalation followed by beta-hydride elimination was favorable over the direct migration of the beta-hydrogen to carbon. Furthermore, our calculations show that the solvent plays an important role in the hydromagnesiation reaction. Furthermore, we have employed an explicit solvent model, where the attachment of one molecule of solvent to the iron center was seen to stabilize the transition states significantly.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: Computational study; Ethylene Assisted Catalysis; EtMgBr Assistance; Explicit Role of Solvent; Hydroformylation; Iron Catalyst